Optimizing community healthcare coverage in remote Liberia. Issue 3 (5th December 2016) - VonAchen, Paige; Smilowitz, Karen; Raghavan, Mallika; Feehan, Ross
Abstract : Purpose: The purpose of this paper is to present a case study describing a collaboration with Last Mile Health, a non-governmental organization, to develop a framework to inform its community healthcare networks in remote Liberia. Design/methodology/approach: The authors detail the process of using the unique problem setting and available data to inform modeling and solution approaches. Findings: The authors show how the characteristics of the Liberian setting can be used to develop a two-tier modeling framework. Given the operating constraints and remote setting the authors are able to model the problem as a special case of the location-routing problem that is computationally simple to solve. The results of the models applied to three districts of Liberia are discussed, as well as the collaborative process of the multidisciplinary team. Originality/value: Importantly, the authors describe how the problem setting can enable the development of a properly scoped model that is implementable in practice. Thus the authors provide a case study that bridges the gap between theory and practice.